An anticipatory life cycle assessment of the use of biochar from sugarcane residues as a greenhouse gas removal technology. (20th August 2021) - Lefebvre, David; Williams, Adrian; Kirk, Guy J.D.; Meersmans, Jeroen; Sohi, Saran; Goglio, Pietro; Smith, Pete
Abstract: Greenhouse gas removal technologies are needed to reach the targets of the UNFCCC Paris Agreement. Among existing technologies, the use of biochar is considered promising, particularly biochar derived from the large quantities of sugarcane residues available in South America and elsewhere. However, the net greenhouse gas removal potential of sugarcane biochar has not been assessed hitherto. We use a scenario-based anticipatory life cycle assessment to investigate the emissions associated with a change from the combustion of sugarcane residues in a combined heat and power plant to the pyrolysis of these residues for biochar production and field application in São Paulo State, Brazil. We define scenarios based on different mean marginal electricity production and biochar production share. The results indicate that emissions from covering the electricity deficit generated by partial combustion of biomass during biochar production is the main emitting process. Overall, the processes associated with biochar production lower the net greenhouse gas benefits of the biochar by around 25%. Our analysis suggests that allocating 100% of the available sugarcane residues to biochar production could sequester 6.3 ± 0.5 t CO2 eq ha −1 yr −1 of sugarcane in São Paulo State. Scaled up to the entire State, the practice could lead to the removal of 23% of the total amount of GHGs emitted by the State in 2016. Highlights: First LCA of sugarcane biochar for GHG removal in Brazil. Covering the energy deficit created by pyrolysis is the most GHG emitting process. Lifecycle emissions reduce the net carbon sequestration benefits of biochar by 25%. Sugarcane residue biochar in São Paulo State, Brazil could sequester 36 Mt CO2 eq yr −1 .